EEG dataset from playing Multiplayer Online Battle Arena games in natural settings - Hong-Zhi Li; Jia-Jia Yang; Zhen Lv; Li-Yang Wan; Wo Wang; Da-Qi Li; Dong-Dong Zhou; Li Kuang (Scientific Data)
Abstract Mobile Multiplayer Online Battle Arena (MOBA) games have emerged as one of the most popular gaming genres, yet the underlying neurophysiological mechanisms contributing to their addictive potential remain unclear. In this study, 23 participants played six real matches of Honor of Kings while synchronized 64-channel EEG recordings were conducted. We provide EEG data collected during gameplay, alongside corresponding video recordings. Additionally, we developed an experimental protocol that accurately marks the timestamps of player kills and deaths within the EEG data. This allows for an investigation of neurophysiological responses to kills and deaths at a millisecond-level time scale within actual MOBA gameplay. Furthermore, we include resting-state EEG data recorded in both eyes-open and eyes-closed conditions, as well as participants’ demographic information and scores related to gaming addiction, impulsivity, and emotional regulation. This dataset aims to contribute to the understanding of neurophysiological responses in natural MOBA gaming environments, providing open access resources with high ecological validity.